Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12639-017-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Zingiber officinale ethanol extract on the viability, embryogenesis and infectivity of Toxocara canis eggs

Abstract: This study evaluated the effect of e (e) ethanol extract on the viability, embryogenesis and infectivity () eggs. It was carried out both in vitro and in vivo. In the in vitro experiment, unembryonated eggs were incubated with 25, 50 and 100 mg/mLe extract at 25 °C for 6, 12, and 24 h to assess the effect of e on their viability and for two weeks to assess the effect ofe on their embryogenesis. In vivo experiment was performed to assess the effect of e on infectivity of eggs. Treated embryonated eggs by extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…El-Sayed observed that Zingiber officinale ethanol extract, with 100 mg/mL concentration has ovicidal activity on T. canis eggs with an efficiency of 98.2% after Mean [1] ± SD [2] Mean ± SD Mean ± SD Mean ± SD 24 hours. The efficacy was 59.22% and 82.5%, respectively, after 24 h, in case of 25, 50 mg/mL concentrations usage [20].…”
Section: Discussionmentioning
confidence: 88%
“…El-Sayed observed that Zingiber officinale ethanol extract, with 100 mg/mL concentration has ovicidal activity on T. canis eggs with an efficiency of 98.2% after Mean [1] ± SD [2] Mean ± SD Mean ± SD Mean ± SD 24 hours. The efficacy was 59.22% and 82.5%, respectively, after 24 h, in case of 25, 50 mg/mL concentrations usage [20].…”
Section: Discussionmentioning
confidence: 88%
“…Usage of glucan with benzimidazoles gave better therapeutic effect in experimental animals (Othman 2012). Nowadays, natural products and medicinal plants are under assessment for the treatment of toxocariasis (Musa et al 2011;El-Sayed 2017). The value of such medicinal plants is related to their therapeutic effect and their use as template molecules for the production of novel drugs.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…The resistance of Toxocara eggs has been tested in studies controlled such as in soil and hair, determining their ability to develop in the hair of dogs, observing that the temperature and moisture factors is responsible for larvae development in eggs, allowing its viability ( 9 ). The disinfection of surfaces contaminated with eggs of T. canis is important because of the public health problem for humans and pets.…”
Section: Introductionmentioning
confidence: 99%